Construction of Knowledge, Attitude and Practice Questionnaire for Assessing Plagiarism - M Mirfakhraei; Z Cheraghi; A Doosti Irani; P Cheraghi; J Poorolajal (Tehran University of Medical Sciences, 2012)
Background: This study was conducted to develop a questionnaire in order to evaluate knowledge, attitude and practice (KAP) of the faculty members and students toward plagiarism.Methods: A KAP study was conducted from June to October 2011 enrolling 390 volunteers anonymously (response rate 96%). The questionnaire included the following four parts: (a) general characteristics like gender, academic degree and education level; (b) nine questions regarding knowledge (Min=0, Max=9); (c) nine questions regarding attitude (Min=9, Max=27); and (d) eight questions regarding practice (Min=0, Max=8). A pilot study was conducted to assess reliability of the questions regarding knowledge and attitude. Cronbach's alpha coefficient for the knowledge and attitude questions was 0.70 and 0.74 respectively.Results: The overall prevalence of at least once plagiarism commission was 38% (SD=0.035). The overall mean score of knowledge, attitude and practice was 5.94 (SD=1.66), 24.12 (SD=2.99), and 0.66 (SD=1.15) respectively. Knowledge of plagiarism was significantly higher among higher academic degrees and females. Their negative attitude toward plagiarism was stronger too. No statistically significant difference regarding plagiarism commission was observed among different academic degrees in both sexes. According to linear regression analysis, plagiarism commission decreased 13% per one unit increase in score of knowledge (P=0.005) and 16% per one unit increase in score of attitude (P<0.001).Conclusions: This knowledge, attitude, and practice (KAP) questionnaire was developed as a standard tool in order to assess perception of subjects toward plagiarism and to estimate the prevalence and the type of plagiarism commission.